Genomic analysis of extensively drug-resistant Acinetobacter baumannii harbouring a conjugative plasmid containing aminoglycoside resistance transposon TnaphA6 - Satoshi Nishida; Yasuo Ono (Elsevier, 2024)
The occurrence of multidrug-resistant Acinetobacter baumannii (MDRA) has increased rapidly and is associated with severe nosocomial infections. MDRA has emerged in the hospital setting and has evolved into extensively drug-resistant A. baumannii (XDRA). A clinical XDRA isolate obtained from a hospitalised patient in 2016 was evaluated for antibiotic susceptibility and whole-genome sequence. The XDRA isolate was resistant to β-lactams, including broad-spectrum cephalosporins and carbapenems, and to aminoglycosides, fosfomycin, fluoroquinolones, tetracyclines, tigecycline, and trimethoprim-sulfamethoxazole. The isolate harboured abaF, ant(3")-II-c, aph(3")-Ib, aph(6)-Id, armA, blaADC-73, blaTEM-1, blaOXA-66, blaOXA-23, mphE, msrE and tet(B). Quinolone resistance was associated with mutations gyrA S81L and parC S84L. Tigecycline resistance was associated with a mutation in adeS. The isolate belonged to Oxford and Pasteur scheme sequence type 1050 and 2, respectively, and harboured a conjugative plasmid containing the aminoglycoside resistance transposon TnaphA6. Our study demonstrates that the isolate is closely related to a recent MDRA identified in Australia and the USA, in which a similar conjugative plasmid is not observed. Although the MDRA in Australia caused an outbreak, our hospital's surveillance protocol managed to prevent a further outbreak. Our finding suggests that this XDRA isolate is of concern in hospital and community care settings. The gpi allele could be a marker for discriminating this isolate from clonal complex 92 isolates.